1993
DOI: 10.1128/aac.37.8.1713
|View full text |Cite
|
Sign up to set email alerts
|

Activity of cationically substituted bis-benzimidazoles against experimental Pneumocystis carinii pneumonia

Abstract: On the basis of a previously observed correlation between the antimicrobial activity and DNA binding strength of dicationic molecules, a series of 10 dicationically substituted bis-benzimidazoles were tested for activity in the rat model of Pneumocystis carinii pneumonia. One of the compounds, 1,4-bis[5-(2-imidazolinyl)-2-benzimidazolyl]butane, was found to be more potent and less toxic than pentamidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 19 publications
(19 reference statements)
1
75
0
3
Order By: Relevance
“…As expected, the monocation 15 does not effectively interact with DNA and it shows no activity against PCP in the immunosuppressed rat model. Compound 8 exhibits the strongest interaction with DNA in this series; analogous results have been noted for the tetrahydropyrimidine cationic center in other similar series of dicationic molcules [20,21]. There is no apparent direct relationship between topoisomerase II inhibition, modeled using the enzyme from Gardia lamblia, and DNA binding or in vivo anti-PCP activity.…”
Section: Biological Results and Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As expected, the monocation 15 does not effectively interact with DNA and it shows no activity against PCP in the immunosuppressed rat model. Compound 8 exhibits the strongest interaction with DNA in this series; analogous results have been noted for the tetrahydropyrimidine cationic center in other similar series of dicationic molcules [20,21]. There is no apparent direct relationship between topoisomerase II inhibition, modeled using the enzyme from Gardia lamblia, and DNA binding or in vivo anti-PCP activity.…”
Section: Biological Results and Discussionsupporting
confidence: 64%
“…Pentamidine and its analogs [19], dicationic bis-benzimidazoles [20,21], and more recently dicationic 2,5-diarylfurans [13] (the latter give calculated radius of curvature values of approximately 15 Å) have been shown to be effective in treating Pneumocystis carinii pneumonia (PCP) and topoisomerase II inhibition may be involved in their mode of action. Collectively, these observations led us to evaluate dicationic 2,4-diarylpyrimidines, which give radius of curvature values in the range predicted to be effective DNA binding agents [17] and which have been demonstrated to strongly bind to AT-rich DNA [14], for effectiveness against PCP.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio was at least 40 for topoisomerase I and 80 for topoisomerase II. It is worth noting that compound 8 was among the most effective compounds in the treatment of PCP in the rat model (41). DISCUSSION The current work originated with studies on pentamidine analogs that clearly showed a correlation between DNA minor groove-binding strength and antiparasitic activity (3).…”
Section: Resultsmentioning
confidence: 99%
“…A P. cariniiinfected rat model has been widely used for examining the efficacy of experimental drugs (3,8,16,19,20). Although this system produces P. carinii pneumonia in immunosuppressed rats 10 weeks earlier than our system, dexamethazone and antibiotics have to be used concomitantly throughout the study.…”
Section: Discussionmentioning
confidence: 99%